Family Planning Practices among Teenage Mothers in Rural Uganda: An Exploratory Study in Bugoye Sub-County (Global Journal of Medical Research, 2020)
Background: Utilization of family planning services among teenagers in resource constrained settings is faced with challenges in regard to proximity to the health facility which is prevalent in rural Uganda. Evidence on the contextual challenges and bottom-top interventions with regard to teenage mothers is limited. This study identified major health related challenges teenage mothers face in a dire need to access family planning services and proposed areas of interventions in rural underserved context of south western Uganda.
Keywords: teenage mothers; rural underserved; family planning; bugoye sub-county; uganda